Zombie dan Diversifikasi Pada Masa Covid-19 - Michelle Fedora; Tan Ming Kuang (Owner : Riset dan Jurnal Akuntansi, 2023)
The financial crisis has caused companies to compete to maintain their financial performance in order to avoid entering the category of "zombie companies." A zombie company is one that has low profits and has experienced losses for several consecutive years. Diversification strategies, such as varying products and/or selling products abroad, are believed to improve a company’s financial performance. This study examines the effect of diversification on zombie companies during the COVID-19 pandemic. The population of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. The sampling technique is purposive, with a sample size of 126 companies. This study uses logistic regression analysis to examine the effect of diversification on zombie companies with tangibility, age, and company size as control variables. The results of this study found that diversification has no effect on zombie companies. As for the control variables of tangibility, age, and company size, they have no effect on zombie companies. This study concludes that both product and market diversification do not help companies avoid zombie conditions during the COVID-19 pandemic. This could be due to the global nature of the COVID-19 pandemic, which hinders the export process in all countries that are mostly affected by the pandemic. Even though product diversification has been carried out, the products offered are still related to products whose sales are still affected by the COVID-19 pandemic.